A Review of Applied Linguistics and its Importance in the Context of English Studies in Nigeria Higher Institution - Olamide, Ijadimine (International Journal For Research In Educational Studies, 2016)
Applied Linguistics is a field of interest to scholars because it depends on insights in other fields such as philosophy and psychology in the teaching of language. Hence, this paper considers a review of Applied Linguistics as an important course of study for English students in Nigeria Tertiary Institutions by considering the context of English as a Second Language(ESL) as an important factor that should guide Applied Linguistics as a course for the students. In addition, questionnaires were administered to students studying English to further shed light on the subject matter. Furthermore, it provides added contribution to academic debate that borders on Applied Linguistics by recommending practical demonstration of theories of language and communication for the training of English as Second Language(ESL)students in Nigeria.